Optimization of Harvesting and Drying Techniques for Quality Seed Production in Specialty Crops: A Systematic Review and Meta-Analysis - Pedrosa, Laura Monteiro [UNESP]; de Almeida Moreira, Bruno Rafael [UNESP]; Martins, Cibele Chalita [UNESP] (MDPI, 2024)
Specialty crops enhance food security, biodiversity, and economic resilience, relying on high-quality seeds. However, there is a gap in understanding how to enhance seed quality under specific conditions. This study addresses this gap by proposing that optimizing harvesting and drying can improve specialty crop seed quality. A literature review spanning 2000–2023 was conducted, followed by a meta-analysis to measure effect sizes. From an initial pool of 1589 documents, 45 met the criteria for further analysis. The results indicated that harvesting seeds at intermediate times significantly increased the logarithmic response ratio (LRR), with LRRs of 1.7 for germination and 2 for seedling count compared with early harvesting. Regarding drying methods, no significant differences were found between artificial and natural methods. However, optimal drying temperatures (30–60 °C) were identified, ensuring adequate moisture levels (10–20%) for a germination percentage of 50–100%. The variability in these findings was attributed to the twelve diverse species analyzed. Although the results supported the study’s hypothesis, limited and inconsistent data prevented the determination of optimal conditions for each species, indicating a need for further research. Despite these limitations, the study provides insights into optimizing harvesting and drying to enhance seed quality in specialty crops, contributing to emerging science in this domain.
Keywords: agricultural economic resilience; farming profitability; sustainable agricultural development; transformative agricultural systems